Response of human pulps following acid conditioning and application of a bonding agent in deep cavities - Costa, CAD; do Nascimento, ABL; Teixeira, H. M. (Elsevier B.V., 2002)
Objectives. The aim of this in vivo study was to evaluate the human dental pulp response when a one-bottle adhesive system was applied on etched or unetched deep dentine.Methods. Eighteen class V deep cavity preparations were divided in three groups: group 1-total etching + two coats of single bond (SB) + composite resin (Z-100); group 2-enamel etching + two coats of SB + Z-100, group 3-cavity floor lined with a calcium hydroxide liner (Dycal) + acid-etching of enamel and lateral walls + two coats of SB + Z-100. Two teeth were used as intact control group. After 30 days the teeth were extracted and processed through H and E, Masson's trichrome and Brown and Brenn staining techniques.Results. Moderate inflammatory response, disorganization of pulp tissue, as well as, deposition of thin layer of reactionary dentin were observed in group 1 teeth in which the remaining dentin thickness (RDT) was less than 300 mum. These histological findings appear to be related to long resin tags formation and bonding agent diffusion through dentinal tubules. In group 2, slight inflammatory response was observed only in one tooth in which the RDT was 162 mum. In group 3, all the teeth showed normal histological characteristics which were similar to the intact control group. Presence of bacteria was not correlated with the intensity of pulpal response. The patients reported no symptoms during the experiment. Radiographic evaluation showed no periapical pathology for any of the teeth,Significance and conclusions. Acid-etched deep dentin (RDT less than 300 mum) lined with SB causes more intense pulpal response than unetched deep dentin. Based on the results observed in the present study and the conditions in which it was carried out, we recommend the application of a biocompatible liner before etching deep dentin and applying SB. (C) 2002 Academy of Dental Materials. Published by Elsevier B.V. Ltd. All rights reserved.
Keywords: adhesive system; acidic agent; dentin; deep cavity; pulp